Pengaruh Ekstrak Kulit Manggis (Garcinia mangostana L.) terhadap Total Haemocyte Count (THC) Udang Vaname (Litopenaeus Vannamei) yang Terinfeksi (Vibrio parahaemolyticus) - Mardiana, Sri; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science; Vol 7 No 2 (2024), 2025)
Vaname shrimp ( Litopenaeus vannamei ) or known as white shrimp is widely cultivated because of it hass a relatively short cultivation period and more resistant to disease. One of the problems of shrimp farming is disease. Prevention of disease in shrimp farming can be performed by giving immunostimulants which the effect of immunostimulants can be seen from the number of haemocyte using total haemocyte count (THC). This study aims to see the effect of mangosteen peel extract ( Garcinia mangostana L . ) on the THC of vannamei shrimp infected with Vibrio parahaemolyticus . The research was conducted at BPIUUK Karangasem, Bali from December 2022 – February 2023 with an experimental method using a 55 l aquarium, filled with an average size of 3.9 g shrimp, with a density of 30 shrimp per aquarium. The experiment consisted of 4 treatments and 3 repetitions, namely P1 (shrimp fed without V. parahaemolyticus infection); P2 (feed + V. parahaemolyticus 10? CFU/ml),; P3 (feed + mangosteen peel extract); P4 (feed + mangosteen peel extract + V. parahaemolyticus 10? CFU/ml). The results showed that the addition of mangosteen peel extract increased the total number of hemocytes significantly (P<0.05) which was significantly different between treatments. However, the addition of mangosteen peel extract when the shrimp were infected with Vibrio resulted in shrimp growth not significantly different (P>0.05) from the other treatments. This indicates that the addition of mangosteen peel extract to feed has the potential as an immunostimulant while increasing survival in vannamei shrimp culture.